1997
DOI: 10.1126/science.277.5327.818
|View full text |Cite
|
Sign up to set email alerts
|

Control of TRAIL-Induced Apoptosis by a Family of Signaling and Decoy Receptors

Abstract: TRAIL (also called Apo2L) belongs to the tumor necrosis factor family, activates rapid apoptosis in tumor cells, and binds to the death-signaling receptor DR4. Two additional TRAIL receptors were identified. The receptor designated death receptor 5 (DR5) contained a cytoplasmic death domain and induced apoptosis much like DR4. The receptor designated decoy receptor 1 (DcR1) displayed properties of a glycophospholipid-anchored cell surface protein. DcR1 acted as a decoy receptor that inhibited TRAIL signaling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
1,315
4
11

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,542 publications
(1,346 citation statements)
references
References 24 publications
16
1,315
4
11
Order By: Relevance
“…Both recombinant, soluble TRAIL and wild-type, membrane-bound TRAIL induce apoptosis in a wide variety of transformed cell lines via interaction with one or both of the death receptors DR4/TRAIL-R1 and DR5/TRAIL-R2, 12,13 which in turn initiates activation of caspase-8 through FADD, leading to apoptosis. [14][15][16] However, the antagonistic decoy receptors DcR1, 17,18 DcR2, 19 and osteoprotegerin 20 are believed to protect normal cells from the cytotoxic effects of TRAIL by competing with DR4/TRAIL-R1 and DR5/TRAIL-R2 for TRAIL binding.…”
Section: In Either Dld1/bax-r or Dld1/trail-r Cells Bcl-xl Expressiomentioning
confidence: 99%
“…Both recombinant, soluble TRAIL and wild-type, membrane-bound TRAIL induce apoptosis in a wide variety of transformed cell lines via interaction with one or both of the death receptors DR4/TRAIL-R1 and DR5/TRAIL-R2, 12,13 which in turn initiates activation of caspase-8 through FADD, leading to apoptosis. [14][15][16] However, the antagonistic decoy receptors DcR1, 17,18 DcR2, 19 and osteoprotegerin 20 are believed to protect normal cells from the cytotoxic effects of TRAIL by competing with DR4/TRAIL-R1 and DR5/TRAIL-R2 for TRAIL binding.…”
Section: In Either Dld1/bax-r or Dld1/trail-r Cells Bcl-xl Expressiomentioning
confidence: 99%
“…Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL, also called APO-2L is a member of the tumor necrosis factor family that appears to induce apoptosis predominantly in transformed cells (Wiley et al, 1995;Sheridan et al, 1997), but also in some normal cells, for example stimulated splenocytes, memory or dendritic cells (Ursini- Siegel et al, 2002;Hayakawa et al, 2004;Janssen et al, 2005). Tumor necrosis factor-related apoptosis-inducing ligand induces apoptosis by binding to one of the two death domain-containing TRAIL receptors, that is DR4 (TRAIL receptor 1) and DR5 (TRAIL receptor 2) (Sheridan et al, 1997). In contrast to humans, mice do not seem to express a receptor homologous to DR4 and the mouse DR5-homolog seems to be the only death-inducing receptor of TRAIL (Wu et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to humans, mice do not seem to express a receptor homologous to DR4 and the mouse DR5-homolog seems to be the only death-inducing receptor of TRAIL (Wu et al, 1999). Tumor necrosis factor-related apoptosis-inducing ligand also binds to the decoy receptors DcR1 (TRAIL-R3) (Sheridan et al, 1997) and DcR2 (TRAIL-R4) , but these receptors contain either no cytoplasmic death domain or a truncated death domain and, therefore, are unable to induce apoptosis. Finally, TRAIL interacts with osteoprotegerin, a secreted soluble protein; however, the functional significance of this interaction is less clear (Emery et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Decoy receptors lack the death domain portion of the molecule, and therefore act as an antagonist to the DR4 and DR5 receptors. 4,[34][35][36][37] In a previous publication we demonstrated that Fas-induced apoptosis is not blocked by overexpression of bcl-2. 30 More recently, we demonstrated that TNF␣-induced apoptosis in myeloma cells is also resistant to bcl-2.…”
Section: Trail Is Not Cytotoxic To Freshly Isolated Cd34 + /Cd45 Dim mentioning
confidence: 89%